2022
DOI: 10.3389/fvets.2022.905382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Traditional Chinese Medicine on the Gut Microbiota in Heat-Stressed Laying Hens

Abstract: Gut microbiota plays an important role in health and disease. To determine whether the traditional Chinese formula Zi Huang Huo Xiang San (ZHHXS) modulates gut microbiota under heat stress, a heat stress model was prepared in Roman layer hens by housing them at temperatures of 32–36°C and administering ZHHXS for 4 weeks. The Roman egg layers were randomly divided into three groups with 10 hens in each: a ZHHXS treatment group (ZHHXS-HS), a heat-stressed group (HS), and a blank control group (BC). The ZHHXS-HS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Similarly, Ye et al found that the gut microbiota composition in layer hens under heat stress could be modulated by a traditional Chinese formula named Zi Huang Huo Xiang San. This formula is comprised of eight dried Chinese herbs: Echinacea root, Scutellaria, patchouli, Elsholtzia, Gypsum, dried tangerine peel, white Atractylodes rhizome, and licorice [ 39 ]. The beneficial effects of these TCMs are attributed to their roles in strengthening the intestinal barrier function, inhibiting the proliferation of deleterious bacteria, augmenting the beneficial bacterial population, modulating immune responses, and increasing antioxidant capacity [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ye et al found that the gut microbiota composition in layer hens under heat stress could be modulated by a traditional Chinese formula named Zi Huang Huo Xiang San. This formula is comprised of eight dried Chinese herbs: Echinacea root, Scutellaria, patchouli, Elsholtzia, Gypsum, dried tangerine peel, white Atractylodes rhizome, and licorice [ 39 ]. The beneficial effects of these TCMs are attributed to their roles in strengthening the intestinal barrier function, inhibiting the proliferation of deleterious bacteria, augmenting the beneficial bacterial population, modulating immune responses, and increasing antioxidant capacity [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This formula is comprised of eight dried Chinese herbs: Echinacea root, Scutellaria, patchouli, Elsholtzia, Gypsum, dried tangerine peel, white Atractylodes rhizome, and licorice [ 39 ]. The beneficial effects of these TCMs are attributed to their roles in strengthening the intestinal barrier function, inhibiting the proliferation of deleterious bacteria, augmenting the beneficial bacterial population, modulating immune responses, and increasing antioxidant capacity [ 38 , 39 , 40 ]. Other studies have indicated that TCMs including Taraxacum , Astragalus membranaceus Bunge, Cnidium monnieri (L.) Cuss, and Taraxacum mongolicum Hand.-Mazz.…”
Section: Discussionmentioning
confidence: 99%